2021
DOI: 10.1186/s12889-021-10990-8
|View full text |Cite
|
Sign up to set email alerts
|

Lung function impairment and cardiometabolic risks among rural adults: implication for an aging society

Abstract: Background Early detection and prevention of cardiometabolic risk factors in an increasingly aging society are a global public health concern. Maintaining adequate lung function is important for healthy aging. Few studies exist on lung function impairment and decline in primary healthcare settings, especially among rural adults with cardiometabolic risks. This study aimed to explore the prevalence of impaired lung function and its association with cardiometabolic risks among rural adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In contrast, only men with abdominal obesity (or increasing WC) and women with dysglycemia (elevating fasting blood glucose) were more likely to develop RVD. Many studies demonstrated that the risk of developing RVD was associated with MetS [7,[19][20][21][22][23][24]. We observed an increased risk of RVD with increasing numbers of metabolic abnormalities, which was consistent with those reported by other researchers [7], [19,25].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, only men with abdominal obesity (or increasing WC) and women with dysglycemia (elevating fasting blood glucose) were more likely to develop RVD. Many studies demonstrated that the risk of developing RVD was associated with MetS [7,[19][20][21][22][23][24]. We observed an increased risk of RVD with increasing numbers of metabolic abnormalities, which was consistent with those reported by other researchers [7], [19,25].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to asthma, betel nuts also associate with COPD, another common type of lung disease caused by chronic inflammation. Lin et al conducted a cross-sectional study of 1653 participants, and their results were the first to suggest a positive correlation between betel nut chewing and obstructive lung disease [10]. The mechanism underlying the association between betel nut chewing and COPD may also be related to arecoline, which can lead to tracheobronchial hypersecretion, tracheal smooth muscle contraction, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, betel nut was recognized by the International Agency for Research on Cancer as a group 1 human carcinogen [7]. In addition, betel nut chewing has been associated with metabolic syndrome, cardiovascular abnormities such as arterial stiffness and coronary artery disease, and the growth of colorectal polyps [8][9][10]. Although many studies have investigated the relationships between betel nut and extrapulmonary abnormalities, little is known about the effects of betel nuts on lung function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a health module in the 2014-2015 wave of the NLSY, participants were asked if they were ever diagnosed with the following cardiovascular and related health problems: (1) stroke, (2) heart problems, (3) high blood pressure, and (4) lung problems. Though lung problems are not technically a CVD, research shows the strong interrelationship between lung impairment and cardiovascular disease (e.g., Lin et al, 2021). Therefore, we also consider lung problems as a related health problem in our analyses.…”
Section: Dependent Variable: Cardiovascular-related Problemsmentioning
confidence: 99%